Impact study of landscape renewal design on neighborhood microclimate based on a structural analysis framework considering global warming scenarios - Xiaohe Xu; Lan Wang; Lulu Liu; Shanshan Wu; Shanshan Wang (Journal of Asian Architecture and Building Engineering)
For highly urbanized and populated nations, building renovations are recognized as economical ways to enhance environmental quality over new constructions. Landscape design, as part of land cover renewal, is a cost-effective option to improve environmental quality and building energy performance by improving microclimate. However, researches on the impact of landscape design on neighborhood microclimate remain insufficient due to its complexity and variability. This paper proposes a structural analysis framework decomposing landscape designs into “ratio”, “pattern”, and “parameters”. Taking an old residential complex in Guangzhou, China, as an example, the impact of landscape design on neighborhood microclimate is analyzed under present and future global warming scenarios with validated ENVI-met models. Results indicate that adjusting the ratio, pattern, and parameters of the landscape can significantly improve the neighborhood microclimate. Increasing the ratio of vegetation to pavement and the albedo of pavement can improve the microclimate. Pattern variations influence outdoor air temperature maps, and increasing pattern uniformity improves microclimate by averaging air temperature. The proposed analysis framework is a robust tool to quantify complex landscape designs, providing valuable references for policymakers and urban designers to create sustainable urban renovation plans.